Pengaruh Ulasan Daring dan Citra Merek Terhadap Kepercayaan Merek pada UMKM Boltapiet di Kota Malang - Agustin Mahardika; Yulis Nurul Aini; Achmad Zaini (Indo Publishing, 2026)
The increasingly tight competition for UMKM, including in Boltapiet UMKM in Malang, requires that consumer trust in brands be maintained. In the digital era, this trust is influenced by daring reviews on social media and brand image formed from consumer perception. This study aimed to determine and analyze the influence of online reviews and brand image on brand trust in Boltapiet UMKM. This research was quantitative research with an explanatory research approach, using questionnaire data collection techniques, observations, interviews, and documentation. The purposive sampling technique was used to obtain 91 respondents. The data analysis used validity, reliability, classical assumption, multiple linear regression, determination coefficient, t-test, and F test with IBM SPSS Statistic. The results study showed that online review spartially have a positive and significant effect on brand trust. Brand image partially has a positive and significant effect on brand trust. In the F test, online reviews and brand image simultaneously had a positive and significant effect on brand trust and online reviews contributed the most dominant. It can be concluded that online reviews and brand image contribute to forming brand trust in Boltapiet UMKM in Malang. Therefore, UMKM need to optimize the management of digital reviews and maintain the consistency of a positive brand image so that consumer trust continues to increase.